The relationship satisfaction of heterosexual couples in one low-income, semi-rural Western Cape community - Engelbrecht, Sarah-Kate (Stellenbosch : University of Stellenbosch, 2009)
ENGLISH ABSTRACT: Effective interventions are hindered by a lack of context-specific data on how South African men and women construct and experience intimate heterosexual relationships. Most studies exploring committed heterosexual relationships have been conducted with White populations living in developed countries. As relationship satisfaction is seen as a requirement for a good quality relationship, this study examined the relationship satisfaction of committed heterosexual couples in one low-income, semi-rural Western Cape community. A cross-sectional survey approach was used to examine relationship satisfaction among heterosexual married and unmarried couples. A random sample of 100 couples was drawn from the community, 93 of which were included in the final analyses, on the criterion that both partners were interviewed. Trained fieldworkers administered a demographic and relationship questionnaire, as well as three relationship satisfaction measures namely the Dyadic Satisfaction subscale of the Dyadic Adjustment Scale, the Index of Marital Satisfaction and the Kansas Marital Satisfaction Scale. Analyses were conducted using the statistical programme Statistica 7.0 and both descriptive and inferential statistics were computed separately for men and women. Inferential statistics included Spearman correlations, repeated measures ANOVA, and reliability analyses. Results show that although, on average, neither men nor women were clinically dissatisfied with their relationships, women reported significantly lower relationship satisfaction than men. Significant relationships were found between relationship satisfaction and a number of demographic variables, including the male partner’s educational attainment (with the female partner’s relationship satisfaction); female partner’s perception of her male partner’s religiosity (with both her own and her male partner’s relationship satisfaction); own church attendance (with own relationship satisfaction), female partner’s church attendance (with her male partner’s relationship satisfaction), and joint church attendance (with both female and male relationship satisfaction); sharing a bedroom at night with children, sharing a bed at night with children, and sharing a bed at night with partner. Demographic variables found to have a non-significant relationship with relationship satisfaction included: age; church affiliation; employment; and couple monthly income. Although there were several trends that tended towards significance, the only relationship variables found to be significantly related to relationship satisfaction were previous marriages and, for cohabiting couples, the age at commencement of cohabitation. Relationship variables found to have a nonsignificant relationship with relationship satisfaction included: relationship status; relationship duration; age at marriage for married couples; reason for marriage (for married couples) or for marriage in the future (for unmarried couples); number of significant relationships; and a number of childrenrelated variables. Results are discussed and recommendations are made for future research.